Purchasing decision optimization strategy by service quality innovation through purchase intention - Abimanyu Tuwuh Sembhodo; Adya Hermawati; Endang Fatmawati; I Wayan Ruspendi Junaedi (Jurnal Inovasi Ekonomi, 2022)
This study aims to understand the behavior of housing buyers. The data collected in this study use a survey method, using the purposive sampling technique to generate 40 respondents. Structural equation modeling (SEM) showed that service quality innovation did not improve purchasing decisions but purchasing intention mediating service innovation and purchasing decision.